Immortality on ice - Engle, Larry; Hayes, Bill.; Wilcher, Deanie; Caliandro, Tom.; Discovery Channel (Firm).; Advanced Medical Productions ([S.l.] Discovery Communications, 1996)
"Offers an intriguing perspective on the strange frozen world of cryonics -- human preservation through freezing in the hope that tomorrow's advanced technology can transcend death, disease and aging -- its supporters and its critics, and its incredible promise of life after death.
Produced by Advanced Medical Productions for Discovery Channel.
Distributed in the Philippines by Magnavision.
Associate producer, Deanie Wilcher ; for Discovery Channel, executive producer, Tom Caliandro ; executive in charge of production: Michael Quattrone.
Keywords: Alcor Life Extension Foundation; Cryonics; Cryobiology; Immortalism